COMMODIFICATION AND FRAMING OF NEWS IN THE ISSUE OF RATIFICATION OF THE RUU TPKS - Lusianawati, Hayu; Syafuddin, Khairul; Qorib, Fathul (ASPIKOM Jabodetabek Region, 2024)
The Sexual Violence Crime Bill (RUU TPKS) was ratified by Indonesia's Parliament (DPR RI) on April 12, 2022, generating significant public interest that peaked between April 10-16, 2022. Online media outlets capitalized on this momentum. This study examines news framing by three media outlets using framing theory and ekspression concepts through qualitative framing analysis. Results show that during April 10-16, 2022, Suaramerdeka.com published 3 articles on RUU TPKS, while Kompas.com published 35 and CNNIndonesia.com published 18. Kompas.com's extensive coverage reflects its business-oriented approach, engaging in commodification practices for political-economic interests. Nevertheless, Kompas.com maintained balanced reporting with sufficient moral content to educate the public about protection for sexual crime victims, unlike CNNIndonesia.com and Suaramerdeka.com, whose coverage lacked moral framing.